Synthesis and characterization of imidazole-substituted calix[4]arenes as simple enzyme-mimics with acyltransferase activity - Schatz, Jürgen; et al. (Tetrahedron Letters, 2001)
Calix[4]arenes which bear imidazole groups at different positions at the wide rim act as catalysts for enzyme-like release of p-nitrophenol from p-nitrophenyl esters in buffered solution. © 2001 Elsevier Science Ltd. All rights reserved.